Mapping the Evolution of Business Ethics and Corporate Governance: A Bibliometric Analysis - Lama, Padam Bahadur; Kharel, Shreekrishna; Karki, Murari; Lamichhane, Basu Dev; Bhatta, Nirjana (Nepal Journal of Multidisciplinary Research, 2025)
Background: Business ethics manifests the moral doctrines, standards, and values guiding the behavioral dimension and decision-making in business entities by adopting fair, socially responsible, and transparent practices. Similarly, corporate governance is the mechanism of rules, procedures, and practices by which an organization is controlled, along with maintaining a balance between the expectations of stakeholders and embracing ethical and accountable business practices. Further, despite gaining paramount interest in business ethics and corporate governance, a summary overview in this area is rare in the literature. Thus, the purpose of this study is to analyze the trends and developments in business ethics and corporate governance research and provide future researchers with novel avenues for investigation in the field. Methods: This research adopted a bibliometric analysis with the use of Bibliometric R Packages (biblioshiny). A total of 336 articles were extracted from lens.org, published from 2001 to 2024 for the analysis. Results: The findings of the study revealed that the increasing trend of research in the field of business ethics and corporate governance was found with a growing trend till 2007 to 2008 and the research, however, increased in a decreasing trend till 2024. Similarly, Business Ethics was the most published research work, the Journal of Business Ethics was depicted as the most published journal, and the highest average annual citation was found in 2008. Next, Fassin was the most cited author and the University of Navarra had the highest publication. Conclusion: This research attempts to demonstrate the evolution and development of business ethics and corporate governance. Therefore, the review contributes to the existing literature on business ethics and corporate governance and offers an opportunity for future research in the field. Novelty: This research demonstrates the growth and trend of study in the field of business ethics and corporate governance, reflecting the major contributors offering the fundamental basis for future research in the field.